Forming the idea of ecological culture and national development in students - Umarov Baxshullo (E3S Web of Conferences)
There is no need to prove the relevance of training young people with intellectual potential in the era of globalization, in the age of information and communication technologies and the Internet, in the era of increasing competition in the world..This article shows the peculiarities of the formation of the idea of the progress of the Fatherland in the process of teaching students to the humanities. Key words: fatherland, progress, idea, spirituality, enlightenment, training, upbringing, perfection, result.